Perception of facial expressions produced by configural relations - V A Barabanschikov; E G Khoze (Peoples' Friendship University of Russia (RUDN University), 2010)
The authors discuss the problem of perception of facial expressions produced by configural features. Experimentally found configural features influence the perception of emotional expression of subjectively emotionless face. Classical results by E. Brunsvik related to perception of schematic faces are partly confirmed.